Model Evaluasi Mata Pelajaran Penjasorkes Dalam Upaya Pengembangan Fisik Dan Karakter Siswa - I Made Sriundy Mahardika (STKIP Al Islam Tunas Bangsa dan HEPI Korda Lampung, 2020)
Abstraction Penjasorkes is one of the compulsory subject in primary and secondary school level. The main task is to improve the physical potential, embed/cultivate sportsmanship and the health of students. In fact these goals hasn't measured as learning outcomes of Penjasorkes. The main cause is because these goals are difficult to measure. In that case, we need to redesign the evaluation model of Penjasorkes to make it user-friendly. Penjasorkes evaluation model that involves the measurement of physical prowess and sportsmanship which designed based on Microsoft Excel. The results of testing at school practice by preservice teacher and school tutor teachers states the program very easy to use and very good in describing the physical quality and character of students. Key word: penjasorkes, Evaluation model,Physical potensial, sport values